Dynamics analysis of Si electrode particle size effect employing accurate Si model. (1st May 2021) - Mu, Ge; Wu, Borong; Ma, Chengwei; Wu, Feng
Abstract: Silicon (Si) experiences tremendous volume change during the lithiation/delithiation process, which is the most serious obstacle to the development of the Si anode in Li-ion batteries. Downsizing Si particles to the nanoscale has always been considered the most effective way to overcome the volume expansion challenge. In this work, the effect of the nano-size and the particle size distribution on the internal dynamics within a battery is studied to clearly understand the Si electrode from the essence. An accurate Si model with multiscale is developed, and the precise Si electrochemical reaction parameters are determined to ensure the accuracy of the Si model. The calibrated model is validated by experimental results reported by the previous studies. Using this useful tool, the dynamic mechanism (potential, solid phase concentration, electrolyte concentration, and electrode utilization) for why decreasing Si size and designing a suitable particle size distribution can improve the cell performance is analyzed.